A multicenter investigation of respiratory syncytial viral infection in children with hematopoietic cell transplantation. Issue 3 (2nd April 2018) - Rowan, Courtney M.; Gertz, Shira J.; Zinter, Matt S.; Moffet, Jerelyn; Bajwa, Rajinder P. S.; Barnum, Jessie L.; Kong, Michele; ,
Abstract: Background: Hematopoietic cell transplant (HCT) may be a risk factor for morbidity and mortality from respiratory syncytial virus (RSV). Previous studies have been limited by small sample size. We took a multicenter approach with the goal of better understanding the epidemiology, risk factors, treatment, morbidity, and mortality associated with RSV infections among children with HCT in the United States. Methods: A retrospective, multicenter, cohort study of pediatric HCT recipients were diagnosed with RSV infection between January 2010 and December 2014. Results: Of the 1522 HCT, 47 (3%) patients were diagnosed with RSV. Of those with RSV, 9 (19.1%) were admitted to the pediatric intensive care unit (PICU), 6 (12.8%) received invasive mechanical ventilation, and 1 died. Prophylactic palivizumab was uncommon. All who required critical care received ribavirin vs 7.3% of those who did not ( P  = .004). Cobacterial infections were found in 16 patients and were not associated with the need for critical care. We examined potential risk factors for severity of RSV disease. In those who received invasive ventilation, 100% had one of the preidentified risk factors. Half of those requiring mechanical ventilation were diagnosed with RSV during their conditioning for transplant as opposed to only 2.4% of those that did not require invasive mechanical ventilation ( P  = .005). Conclusions: In this multicenter cohort, RSV was not common in children following HCT. Few children infected with RSV required critical care and mortality was low. Those diagnosed with RSV during conditioning for transplant were at higher risk for invasive mechanical ventilation.